Toward a Digitalized Economy: The Impact of Digital Index Performance on The Economic Growth in Indonesia - Rahmayani, Dwi; Abdulah, Rusli; Suseno, Deky Aji (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
Nowadays, the world relies heavily on digitalization. This study aims to analyze the effect of digitalization on economic growth in Indonesia. This study used panel data from 32 provinces in Indonesia, ranging from year 2017 to 2023. This study employed fixed and dynamic panel models with economic growth as the dependent variable and stock of capital and labor digitalization as independent variables. Digitalization is proxied by the access and infrastructure sub-index, the usage sub-index, and the skills sub-index. The estimation result shows that variables of stock of capital, labor, and digital economic development in Indonesia positively affect economic growth, and we also find that heterogeneity effects exist between different provinces. However, there is no significant effect on the dynamic panel models on generalized method moment. The results draw three implications: increasing investment in physical capital stock, improving human capital quality, and promoting Information and Communication Technology (ICT) readiness.